THE MACROECONOMIC ENVIRANMENT OF THE FOOD INDUSTRY IN IRAQ AND ITS FUTURE PROSPECTS - محمدعلي سلامة نعمة; نظمي داليا عمر (Journal of Economics and Administrative Sciences, 2017)
Food industries are variety to include number of agricultural products (plantbotential and animal) which can be manufactured locally, thus, Iraqi market is full by different types of food products from neighbor countries, because of un equivalence and inability of competence, in away to cover (90%) average of local request need under commercial opening. In Iraq although its importance, this industry suffers from difficulties, the most important one is the rising in products costs, shortage in agricultural products, experience, and qualification, besides, the challenges , by flooding market in food products and what are contained of higher competitive features from quality and prices sides . So, it is determined the government to be active in this field to give its more care for private sector especially (agricultural product and food manufacturing), and providing necessitate supporting, assisting, protecting, which are mentioned at the recommendations of the research.